An Application of Smart Building Concept for Historical Building Using Automatic Control System. Case Study: Fatahillah Museum - Ari Widyati Purwantiasning; Saeful Bahri (Department of Architecture Universitas Muhammadiyah Jakarta, 2017)
An activity of conservation for an old historical building has become an important issue nowadays in Indonesia, particularly in Jakarta. One of the concepts is by implementing the concept of a smart building into an old historical building using a concept which could maintain economically and financially. Some old historical buildings within Jakarta have been revitalized with a new function which is known as an adaptive reused concept. Although, this concept has been regarded not effectively implemented to reduce energy consumption. To solve this problem, this research will deliver an alternative solution by introducing the application of smart building concept within an old historical building using automatic control system. This system will cover the air conditioning and lighting system within the building. This research will conduct a comparative method from some precedent studies and will use an inductive approach. At the final phase, this research will provide a solution design by simulating the using of an automatic control system within an old historical building.